Analisis Perilaku Hidup Bersih dan Sehat dengan Kejadian Penyakit Diare pada Anak di Kecamatan Meurah Mulia Kabupaten Aceh Utara - Muslim Amin; Natasya Faezah Aqilla (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Diarrhea is one of the main health problems in developing countries, especially in Indonesia, which can be prevented through implementing Clean and Healthy Living Behavior (PHBS). This study aims to analyze the relationship between PHBS and the incidence of diarrhea in children under five (aged 0-5 years) in Meurah Mulia District, North Aceh Regency. The research method uses a quantitative descriptive approach with data collection techniques in the form of questionnaires, interviews and direct observation of 100 mothers of toddlers. The variables studied included the use of clean water, the habit of washing hands with soap (CTPS), and the use of healthy latrines. The results of the study showed that there was a significant relationship between PHBS and the incidence of diarrhea. As many as 21.4% of children from the group that used clean water experienced diarrhea, while this figure increased to 83.3% in the group that did not use clean water. In addition, only 16% of children in the group who did CTPS experienced diarrhea, compared to 84% in the group who did not do CTPS. Meanwhile, the use of healthy latrines also showed a significant effect, with 16.7% of children who used healthy latrines experiencing diarrhea, compared to 75% in the group who did not use healthy latrines.